MEDICINAL HERBS IN IRANIAN TRADITIONAL MEDICINE FOR LEARNING AND MEMORY - Shojaii, Asie; Ghods, Roshanak; Fard, Mehri abdollahi (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: There are some factors such as age, stress and emotions that may lead to impaired learning, memory loss, amnesia, and dementia or threats like Schizophrenia and Alzheimer’s disease (AD). Traditional Iranian medicine (TIM) recommended some herbs and herbal preparations for treatment or prevention of CNS problems. In this study, the scientific evidences related to effectiveness of TIM herbal medicine on memory and learning will be reviewed. Materials and Methods: The scientific evidences of the plant efficacy were searched in electronic databases including Pub Med, Scopus, SID, Science Direct, and Google Scholar by keywords like memory, Alzheimer, amnesia, learning and scientific plant names from 1969 to 2014. Results: The finding of this study confirmed effectiveness of some of TIM medicinal plants on enhancing memory and learning or in treatment or prevention of amnesia and AD. Some of TIM plants like Melissa officinalis, Crocus sativus and Nigella sativa showed improving effect on memory in clinical trials. In some cases, the active principles responsible for efficacy of these plants on memory were also determined. Conclusion: Most of the studies on TIM plants were designed in animal models and a few herbs were evaluated in clinical trials on AD. Also, for some of the herbal medicine used in TIM, there are no or not enough studies to confirm their effectiveness on memory and learning. Therefore, further experimental and clinical studies are necessary to evaluate the effectiveness of these plants on memory and AD and also to determine the active components of them.